The Relationship Between Self-Esteem and Psychological Well-Being Among Adolescent Victims of Bullying in Junior High School - Nike Riskia Anjani; Mariyati Mariyati; Wijanarko Heru P (Lembaga Pengembangan Kinerja Dosen, 2025)
Bullying is an intentional aggressive action or behavior, carried out by a group of people repeatedly and from time to time against a victim who cannot defend himself easily or as an abuse of power or strength . Bullying is also a serious problem among teenagers that has a direct impact on the psychological condition of the victim, especially on aspects of self-esteem and psychological well-being. This study aims to analyze the relationship between self-esteem and psychological well-being in adolescent victims of bullying in junior high schools . This type of research uses a non-experimental design with a cross-sectional approach that is included in the type of descriptive correlational research with 63 research subjects. Simple sampling in the study used a purposive sampling method calculated by the Slovin formula and produced 54 samples. The instruments used were the Rosenberg Self-Esteem Scale (RSES) to measure self-esteem and the Psychological Well-Being Scale for Children (PWB-C) to measure psychological well-being. Data were analyzed using the Spearman Rank test, the results of the study showed a p-value = 0.000 (p < 0.05) and r = 0.550, which means there is a significant positive relationship between self-esteem and psychological well-being in adolescent victims of bullying . The higher the adolescent's self-esteem, the better their level of psychological well-being.